2007
DOI: 10.1007/s00213-007-0867-z
|View full text |Cite
|
Sign up to set email alerts
|

Platelet MAO activity and the 5-HTT gene promoter polymorphism are associated with impulsivity and cognitive style in visual information processing

Abstract: The two markers of lower serotonergic capacity, 5-HTTLPR S allele and low platelet MAO activity, have a similar and partly synergistic influence on self-reported as well as performance measures of impulsivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 63 publications
4
56
0
1
Order By: Relevance
“…However, two MAOA gene haplotypes in the MAOA gene (Jansson et al 2005), as well as polymorphism on the promoter region of the 5-HTT gene (Paaver et al 2007) were shown to be associated with lower platelet MAO activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, two MAOA gene haplotypes in the MAOA gene (Jansson et al 2005), as well as polymorphism on the promoter region of the 5-HTT gene (Paaver et al 2007) were shown to be associated with lower platelet MAO activity.…”
Section: Discussionmentioning
confidence: 99%
“…Ela tem se mostrado útil na identificação de diferentes padrões de impulsividade em diversas patologias, como o transtorno do déficit de atenção e hiperatividade 3 , o transtorno afetivo bipolar 17 , a esquizofrenia 18 , o transtorno por uso de substância 19 , o jogo patológico 3 , entre outras. Além disso, tem sido bastante útil em estudos em neurobiologia da impulsividade 20 , bem como em estudos sobre outros construtos neuropsicológicos relacionados à impulsividade, tais como funções executivas 21 , atenção 22 e sensibilidade ao reforço 23 . Deve ser salientado ainda que o modelo proposto por Barratt apresenta importante relação com outros modelos em neurociências sobre impulsividade [2][3] e sobre aspectos anatomofuncionais dos circuitos pré-frontais, como no modelo proposto por Fuster 24 .…”
unclassified
“…Studies on the association between impulsivity and the polymorphic variants of 5HTTLPR in humans found rather controversial results [30]: many studies describe a significant association between impulsivity and the s-allele of 5-HTTLPR [41,51,57] but about as many studies do not find such a relationship [44,48,58]. As a whole, it may be not surprising that the s-allele could be associated with more impulsive performance in clinical research, given the anatomical complexity of the serotonergic projections, the variety of receptor families and subtypes, and the consequential breadth of its functions.…”
Section: Discussionmentioning
confidence: 99%
“…[8,55]). However, in humans, an increase in impulsivity appears to be associated with the short (s) allelic variant of 5-HTTLPR, leading to reduced SERT gene transcription [41,51,57]. Thus, we aimed to determine whether a partial silencing of the SERT-encoding gene within the hippocampus could induce alterations relevant to the modelling of ADHD, in particular symptoms of hyperactivity and impulsivity.…”
Section: Introductionmentioning
confidence: 99%